2016
DOI: 10.1017/jfm.2016.2
|View full text |Cite
|
Sign up to set email alerts
|

Dynamic-mode decomposition based analysis of shear coaxial jets with and without transverse acoustic driving

Abstract: Modal decompositions of unperturbed and acoustically driven injector flows from shear coaxial jets are implemented using dynamic-mode decomposition, which is a natural approach in the search for collective oscillatory behaviour in nonlinear systems. Previous studies using proper orthogonal decomposition had revealed the most energetic pairs of coherent structures in injector flows. One of the difficulties in extracting lower-energy coherent structures follows from the need to differentiate robust flow constitu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
13
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 39 publications
(13 citation statements)
references
References 20 publications
0
13
0
Order By: Relevance
“…In parallel, progress has also been made regarding the inclusion of the effects of waves in coupled ocean-sea ice models. Using a very simple parameterization, Steele et al (1989) and Perrie and Hu (1997) have investigated the ef-fect of WRS on sea ice drift in the MIZ, only considering the attenuation of waves generated between the ice floes, and found a limited impact on the sea ice conditions. More recently, Williams et al (2017) implemented a wave module in the semi-Lagrangian sea ice model neXtSIM (Rampal et al, 2016) and found that high-wave conditions can cause a significant displacement of the sea ice edge.…”
Section: Introductionmentioning
confidence: 99%
“…In parallel, progress has also been made regarding the inclusion of the effects of waves in coupled ocean-sea ice models. Using a very simple parameterization, Steele et al (1989) and Perrie and Hu (1997) have investigated the ef-fect of WRS on sea ice drift in the MIZ, only considering the attenuation of waves generated between the ice floes, and found a limited impact on the sea ice conditions. More recently, Williams et al (2017) implemented a wave module in the semi-Lagrangian sea ice model neXtSIM (Rampal et al, 2016) and found that high-wave conditions can cause a significant displacement of the sea ice edge.…”
Section: Introductionmentioning
confidence: 99%
“…Broken ice floes [e.g., Meylan et al, 1997;Montiel et al, 2016] or variations in ice thickness [Squire et al, 2009;Bennetts and Squire, 2012] may scatter wave energy in all directions thereby enhancing the wave attenuation. Alternatively, the breaking of ice into small floes reduces the deformations of the ice layer, resulting in less creep-induced dissipation of wave energy, possibly explaining the weak attenuation of waves in broken ice reported by Collins et al [2015], compared to similar wave conditions in unbroken ice.…”
Section: Introductionmentioning
confidence: 99%
“…Most of the recent efforts in the modeling community have been focusing on the impact of sea ice on waves, leading to the development of wave models accounting for the presence of sea ice (Dumont et al, 2011;Williams et al, 2013;Montiel et al, 2016;Boutin et al, 2018). By prescribing sea ice conditions, these models are able to reproduce accurately the time and space variations of wave height in sea ice retrieved from recent field observations (Kohout et al, 2014;Thomson et al, 2018;Cheng et al, 2017) and innovative processing of Synthetic Aperture Radar (SAR) satellite observations (Ardhuin et al, 2017).…”
mentioning
confidence: 99%